2006
DOI: 10.1093/bja/ael004
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of Bispectral Index™ and A-Line™ Autoregressive Index™ to assess anti-nociceptive component of balanced anaesthesia during lumbar arthrodesis

Abstract: During a BIS-guided constant level of hypnosis, AAI response to the onset of surgical stimulation significantly differs according to the analgesic regimen. Further studies are needed to refine the estimation of sensitivity and specificity of this variable in assessing the balance between nociception and anti-nociception during general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Second, the BIS increase observed in the present study was associated with an increase in EEG amplitude and a decrease in EEG suppression ratio, reflecting EEG activation, as already observed by Visser et al 10 in their study on the patterns of spectral EEG changes during carotid clamping. Third, the BIS increase was associated with an increase in AAI, which may be indicative of impaired control of nociception, 19 or lightening of the hypnotic state. In addition, it was also associated with a shorter delay between induction of anesthesia and CXC.…”
Section: Increase In Bismentioning
confidence: 99%
“…Second, the BIS increase observed in the present study was associated with an increase in EEG amplitude and a decrease in EEG suppression ratio, reflecting EEG activation, as already observed by Visser et al 10 in their study on the patterns of spectral EEG changes during carotid clamping. Third, the BIS increase was associated with an increase in AAI, which may be indicative of impaired control of nociception, 19 or lightening of the hypnotic state. In addition, it was also associated with a shorter delay between induction of anesthesia and CXC.…”
Section: Increase In Bismentioning
confidence: 99%
“…Effective regional techniques in the hands of skilled clinicians can ablate the peak noxious barrage (Bonhomme et al, 2006; Wennervirta et al, 2011) of pain in the perioperative period and potentially minimize pathological neural plasticity implicated in the genesis of chronic pain (Woolf and Salter, 2000; Scholz and Woolf, 2007; Harvey and Dickenson, 2008; Ivani et al, 2011). Unsurprisingly, the majority of the trials included in this review found regional analgesia to be beneficial for reducing perioperative pain and subsequent chronic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…AEP provides information about the function of the brainstem and subcortical and cortical components, showing the overall anesthetic state. [9] Because BIS measures cortical function, it is only able to monitor hypnotic state and is a poor indicator of the sensitiveness to pain. [10] Therefore, the AAI and not the BIS increased by intubation in the present study as in our previous studies.…”
Section: Discussionmentioning
confidence: 99%